Optimization of immunization procedure for SWCNTs‐based subunit vaccine with mannose modification against spring viraemia of carp virus in common carp - Gong, Yu‐Ming; Zhang, Chen; Li, Yang; Chen, Guo; Wang, Gao‐Xue; Zhu, Bin (Journal of fish diseases, 2021)
Immersion vaccination of single‐walled carbon nanotubes loaded with mannose‐modified glycoprotein (SWCNTs‐MG) vaccine has been proved to be effective in preventing spring viraemia of carp virus (SVCV). Immunization procedure has immense consequence on the immune effect of the immersion vaccine. However, immunization procedure optimization for SWCNTs‐MG vaccine against SVCV has not been reported. In this study, accordingly, a full‐factor experiment was designed to optimize the immunization procedure of SWCNTs‐MG vaccine by three aspects of vaccine dose (30 mg/L, 40 mg/L and 50 mg/L), immunization density (8 fish L−1, 24 fish L−1 and 48 fish L−1) and immunization time (6, 12 and 24 hr). Furthermore, we used the immunization group (A1B2C1, 30 mg/L, 24 fish L−1 and 6 hr) in the previous study as a positive control (PC) to evaluate the immunization effect optimized conditions from the expression of immune‐related genes and relative percentage survival (RPS). At 28 days post‐vaccination (DPV), common carps were intraperitoneal injected SVCV challenged test indicated that the A1B2C2 group (30 mg/L, 24 fish L−1, 12 hr) displayed superiority of protective efficacy compare with other groups and the RPS with 77.9%, which was 15.6% higher than the PC group of RPS with 62.3%. Moreover, the expression of immune‐related genes such as IL‐10, CD4 and MHC‐II was also significantly higher than PC group. The specific experimental flow chart is shown in Figure 1. Conclusively, these results demonstrated that vaccine dose, immunization density and immunization time are 30 mg/L, 24 fish L−1 and 12 hr, which is the more appropriate immunization programme with juvenile carp for SWCNTs‐MG vaccine. This study provides a profitable reference for improving the immune efficiency of aquatic immersion vaccine. 1 FIGURE The experiment process and timeline chart of the present research